Low Substrate Temperature Encapsulation for Flexible Electrodes and Organic Photovoltaics. Issue 6 (2nd December 2014) - Chen, Nan; Kovacik, Peter; Howden, Rachel M.; Wang, Xiaoxue; Lee, Sunghwan; Gleason, Karen K.
<x xml:space="preserve">Abstract</x> Encapsulation is of key importance to improve the stability and lifetime of organic conductors and devices, mainly in applications such as flexible electrodes or organic photovoltaics (OPV). Here, a single‐layer conformal encapsulation method is demonstrated via initiated chemical vapor deposition (iCVD) for organic conductor, poly (3, 4‐ethylenedioxythiophene) (PEDOT). The accelerated degradation tests at 100 °C show that the conductivity of encapsulated PEDOT can be retained up to 17 times longer than that of the unencapsulated counterpart. PEDOT degradation and encapsulation mechanisms are also discussed. Furthermore, the versatility of the iCVD encapsulation on a top‐illuminated OPV architecture that can be used to produce low‐cost photovoltaics devices on various unconventional substrates (e.g., paper) is demonstrated. Unlike previous approaches of using solely water/oxygen barriers, the encapsulation effect of polymer films on OPV devices is improved by a thin layer capping of evaporated UV‐screening material, Cerium(IV) oxide (CeO2) over the iCVD polymer layer. This bilayer encapsulation strategy efficiently slows the degradation of OPVs and represents a new method to encapsulate OPV and other organic devices.